The Role of Payoff Valence on Voting: Egalitarian for Gains and Selfish for Losses - Alós-Ferrer, Carlos; Garagnani, Michele; García-Segarra, Jaume (Frontiers in Psychology, 2021)
We study how payoff valence affects voting behavior on the distribution of monetary outcomes framed as gains or losses in a group when using standard (plurality) voting procedures and when using approval voting. The latter method allows the subjects to approve of as many alternatives as they wish and has been shown to eliminate the incentives to vote strategically. For both methods, we observe that voters express higher support for egalitarian allocations (and lower support for selfish options) when sharing gains than when sharing losses. Moreover, the average number of approved alternatives per ballot is higher when distributions are framed in terms of gains than when they are framed in terms of losses. We also discuss under which circumstances the shift in voting behavior is more likely to produce changes in the electoral outcome. The results suggest that framing manipulations (payoff valence) can significantly impact voting behavior.